2020
DOI: 10.3390/pharmacy8010005
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude Towards Antibiotic Usage: A Questionnaire-Based Survey Among Pre-Professional Students at King Saud bin Abdulaziz University for Health Sciences on Jeddah Campus, Saudi Arabia

Abstract: Introduction: Knowledge and attitudes towards proper antibiotic usage among students in medical and other health allied fields play a vital role in limiting the pandemic of antibiotic resistance. This study aimed to assess knowledge and attitudes toward antibiotic usage among pre-professional students at King Saud bin Abdulaziz University for Health Sciences on Jeddah Campus, Saudi Arabia. Methods: A self-administered cross-sectional survey of 347 first year students was conducted at the College of Science and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 23 publications
(41 reference statements)
6
21
2
2
Order By: Relevance
“…Nearly half of our survey respondents (46.6%) agreed that influenza could be treated with antibiotics. The current research is in concordance with a study conducted in Saudi-Arabia, which reported that more than one-fourth of respondents (medical students) wrongly perceived that antibiotics are useful against viral infections [ 27 ]. Unfortunately, the use of antibiotics in viral diseases such as influenza is widespread in the community and hospitals [ 28 ], which could be due to a lack of optimum antibiotic-related knowledge among healthcare workers and the public [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…Nearly half of our survey respondents (46.6%) agreed that influenza could be treated with antibiotics. The current research is in concordance with a study conducted in Saudi-Arabia, which reported that more than one-fourth of respondents (medical students) wrongly perceived that antibiotics are useful against viral infections [ 27 ]. Unfortunately, the use of antibiotics in viral diseases such as influenza is widespread in the community and hospitals [ 28 ], which could be due to a lack of optimum antibiotic-related knowledge among healthcare workers and the public [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…These differences can undoubtedly be explained by the fact that students of biomedical sciences have much more theoretical knowledge on the subject than ones from the other faculties. Compared to a study done in Saudi Arabia [21], students from Serbia from both groups have been more successful in identifying drugs. In Saudi Arabia, as much as 74% have not been sure about the nature of Paracetamol.…”
Section: Knowledge On Antibioticscontrasting
confidence: 58%
“…Besides, a multitude of studies conducted in Asia has reported much larger percentages of students of medicine or pharmacology employing antibiotics in this fashion. These include Saudi Arabia (64.2%) [21], Qatar (62%) [22], and Sri Lanka (57%) [23]. This shows that biomedical students from Nis University have a better perception of the subject.…”
Section: Knowledge On Antibioticsmentioning
confidence: 92%
“…Those who did not obtain advice are more likely to stop taking antibiotics when they feel better, which eventually leads to the growth of resistance in the community. Respondents also reported obtaining antibiotics from the previous use, but the rate was lower than in the previous studies in Malaysia (46/204), Qatar (161/596), China (1,965/11,192), and Saudi Arabia (165/347) [ 25 , 26 , 27 , 28 ]. There were more female students than male in this study, which is comparable to many other studies [ 8 , 25 , 29 ].…”
Section: Discussionmentioning
confidence: 73%
“…Multiple studies have been conducted regarding the knowledge of antibiotics and antimicrobial resistance among university students in other countries [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. A study among undergraduate students in Sri Lanka revealed that senior students had good knowledge of antibiotics and antimicrobial resistance, although some had misconceptions about antibiotic use for viral illnesses [ 26 ].…”
Section: Introductionmentioning
confidence: 99%